Improvement of Gasoline Octane Number Produced from Basrah Refinery Plant by New Additives - Raheem, A. Z.; Alfalze, M. M.; Mehdi, H. A. (Basrah Journal for Engineering Sciences, 2008)
Basrah Refinery Plant produces recently gasoline with low octane number reached to 75.5, 69.0 for leaded and unleaded gasoline respectively. These fuel causes severe damage to engines and also causes bad fuel combustion which increases air pollution due to the high percentage of [CO] and [CO2] in the exhaust produced. In this research it is tried to improve the gasoline octane number by new chemical additives [aromatic hydrocarbons, aliphatic and aromatic amines] with different percentages in gasoline. This kinds of additives can also be used as antioxidants, antirust and anticorrosion which reduces the total amount of chemicals added to gasoline. The better results obtained with aromatic amines as chemical additives which caused increasing in octane number up to [95-5, 88..0] for leaded and unleaded gasoline respectively. The percentages of [CO] and [CO2] gases formed after combustion are measured by orsat analysis based on dry analyses.